2013
DOI: 10.1021/ac403646n
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Quenching of Carbon Nitride Nanosheet through Its Interaction with DNA for Versatile Fluorescence Sensing

Abstract: This work investigates the interaction of carbon nitride nanosheet (CNNS), a recently developed two-dimensional nanomaterial, with DNA and its fluorescence quenching mechanism on fluorophore labeled single-stranded DNA probes. The static quenching through the photoinduced electron transfer (PET) from the excited fluorophore to the conductive band of CNNS is identified. Utilizing the affinity change of CNNS to DNA probes upon their recognition to targets and the PET-based fluorescence quenching effect, a univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
162
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(164 citation statements)
references
References 46 publications
2
162
0
Order By: Relevance
“…P1/P2-CNNS (200 μg/ml) was incubated with different concentrations (0, 0.5, 25, 100, 200, 300, 400, or 600 pM) of miR-106a in SPSC buffer for 4.0 h at room temperature, the fluorescence measurements were performed using a RF-5301PC spectrofluorometer. ( Figure S1), [29,31] which indicated that FAM-P1 and FAM-P2 were assembled on CNNS, thus a successful preparation of the nanoprobe was confirmed.…”
Section: In Vitro Fluorescence Quantitative Detection Of Mirnamentioning
confidence: 83%
See 1 more Smart Citation
“…P1/P2-CNNS (200 μg/ml) was incubated with different concentrations (0, 0.5, 25, 100, 200, 300, 400, or 600 pM) of miR-106a in SPSC buffer for 4.0 h at room temperature, the fluorescence measurements were performed using a RF-5301PC spectrofluorometer. ( Figure S1), [29,31] which indicated that FAM-P1 and FAM-P2 were assembled on CNNS, thus a successful preparation of the nanoprobe was confirmed.…”
Section: In Vitro Fluorescence Quantitative Detection Of Mirnamentioning
confidence: 83%
“…P1/P2-CNNS was prepared by assembling P1 and P2 onto the CNNS surface through strong π-π interactions (Scheme 1a). [28,29] Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that g-C 3 N 4 exhibits excellent biocompatibility and nontoxicity [33]. In comparison to the graphene oxide, the g-C 3 N 4 dispersion in water showed a stronger Tyndall effect than that of graphene oxide, indicating its excellent stability [34]. The good dispersity, biocompatibility, and nontoxicity of g-C 3 N 4 were favorable for studying its interaction with biomolecules and its application in the biosensing field.…”
Section: Choice Of Materialsmentioning
confidence: 89%
“…Recently, Bojdys and coworkers presented a crystalline triazine-based graphitic carbon nitride with very low hydrogen content (0.51 wt%) and a carbon-tonitrogen ratio close to the theoretical one for g-C 3 N 4 [15]. Owing to their optoelectronic properties, these polymers have nonetheless found potential applications, from light-induced catalysis including hydrogen evolution from water [16,17] to chemical sensing [18,19] and electronic devices [15,20]. Advancement in these applications hinges on the detailed characterization of their physical properties, which so far have been limited due to difficulties in material processing.…”
Section: Introductionmentioning
confidence: 94%